Evaluation of SBDP145, melatonin, sLOX-1, HMGB1 and HIF-1α in preterm infants with brain injury - Sisi Cheng; Xiao Sun; Yanyan Li; Yan Dong (BMC, 2024)
Abstract Background Prematurity-related brain injury is a common and serious complication that has long-term effects on the survival and development of affected infants. Currently, the roles of certain biomarkers such as the protein hydrolysis product SBDP145, melatonin, soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1), high mobility group box 1 protein (HMGB1), and hypoxia-inducible factor 1-alpha (HIF-1α) in prematurity-related brain injury remain not fully elucidated. Our study aims to assess the significance of SBDP145, melatonin, sLOX-1, HMGB1 and HIF-1α in preterm infants with brain injury. Methods 135 preterm infants admitted to our hospital from January 2020 to February 2022 were selected and divided into 78 cases in a prematurity-associated brain injury group, and 57 cases in another group of preterm infants without brain injury or other diseases according to the magnetic resonance imaging results. The levels of SBDP145, melatonin, sLOX-1, HMGB1 and HIF-1α in the two groups were analyzed. The serum concentrations of SBDP145, melatonin, sLOX-1, HMGB1 and HIF-1α in newborns with different severity of ventricular hemorrhage were observed, and the levels of SBDP145, melatonin, sLOX-1, HMGB1 and HIF-1α in those with different severity of white matter brain injury were compared. Results The levels of SBDP145, sLOX-1, HMGB1 and HIF-1α were significantly higher in the preterm combined brain injury group than in the preterm group, and melatonin levels were significantly lower than in the preterm group(P < 0.05). The levels of SBDP145, sLOX-1, HMGB1 and HIF-1α were higher in the moderate to severe group and melatonin levels were lower in the mild group of newborns with ventricular hemorrhage (P < 0.05). The levels of SBDP145, sLOX-1, HMGB1 and HIF-1α were higher in the moderate-severe group and melatonin levels were lower in the mild group in newborns with cerebral white matter injury (P < 0.05). The independent variables were SBDP145, melatonin, sLOX-1, HMGB1, HIF-1α, and the dependent variable was the prognosis of neonates with brain injury. Univariate logistic regression analysis and multivariate logistic regression analysis were performed. The results showed that the influencing factors of newborns with brain injury were SBDP145, melatonin, sLOX-1, HMGB1, HIF-1α. Conclusion The levels of SBDP145, melatonin, sLOX-1, HMGB1 and HIF-1α were highly expressed in preterm newborns with brain injury, and the levels were higher when the condition of the newborns was more severe. These findings suggest the potential clinical utility of these biomarkers in predicting and monitoring brain injury in preterm infants, which could aid in early intervention and improve long-term outcomes.